Diseño de una estructura organizacional y funcional para la empresa embotelladora de agua purificada “Leving Corporation S.A.” del cantón Huaquillas, provincia de El Oro. - Sacotto Loor, Fernando Xavier (2023)
In the context of the company Leving Corporation S.A., challenges related to the lack of a clear organizational structure, the absence of function manuals, the lack of internal policies and the lack of occupational health and safety regulations were identified. These aspects affected the work climate, the delimitation of functions and the performance of the employees. Due to this, the main objective of this study was to evaluate the impact of specific measures on the management of the company's human talent, including the restructuring of the organization, the development of function manuals, the implementation of internal work regulations, the creation of an induction manual and the adoption of occupational health and safety regulations. The research was carried out through a mixed approach that included documentary analysis, interviews with management and employees, and the application of surveys to collect relevant data on the perception of personnel about the organizational structure. The results revealed that most of the workers were not familiar with the existence of a manual of functions or a clear organic-functional structure. Based on these findings, it was proposed the implementation of measures such as the restructuring of the organization, the development of function and induction manuals, internal work and safety regulations, which would contribute to clearly delimit the responsibilities of employees, promote a greater organization and planning, promote a harmonious and safe work environment, improve communication and coordination between departments, as well as strengthen the image and reputation of the company. Keywords: Organizational structure, function manuals, bottling company, company